Analisis Faktor Penyebab Terjadinya Peningkatan Kasus Tuberkulosis di Makassar - Rahmat Hidayat; Al Ikhsan Agus; Andi Surahman Batara; Nasrullah Nasrullah; Muhammad Hisyam (PT.Mantaya Idea Batara, 2024)
Indonesia has made efforts to control tuberculosis but the results have not shown significant changes. The Directly Observed Treatment Shortcourse (DOTS) strategy has been implemented by the government for decades, but the number of sufferers remains high. The DOTS strategy has not been able to overcome the factorsthat cause tuberculosis because each region has different causal factors, therefore it is important to know what factors most influence the incidence of tuberculosis in Makassar. This research is a quantitative study with a crosssectional study design. The research was carried out in the working area of the Makassar Rappokalling Community Health Center. The population is tuberculosis patients who are undergoing treatment. The total sample was 109 respondents. Of the 109 respondents, 88 (80.7%) had a history of contact with tuberculosis sufferers, 85 (78.0%) had poor nutritional status, 81 (4.3%) had poor behavior in preventing transmission, 59 (54.1%) lacked knowledge. %), lack of family support 79 (72.5%) and feel high levels of societal stigma 91 (83.5%). The results of the KMO analysis are >0.50, which means that the factors that influence the incidence of tuberculosis cases are, sequentially, nutritional status (0.0795), history of contact with sufferers (0.776), behavior to prevent transmission (0.763), knowledge (0.726), public stigma (0.678) and family support (0.639). Factors such as nutritional status, history of contact with sufferers, behavior to prevent transmission, knowledge, community stigma and family support are factors that cause the incidence of tuberculosis and can be the cause of the increase in the number of tuberculosis cases in Makassar.